Niedzwetzky’s apple (Malus niedzwetzkyana Dieck): evaluation and breeding prospects - O. N. Barsukova (Труды по прикладной ботанике, генетике и селекции)
Background. Niedzwetzky’s apple (Malus niedzwetzkyana Dieck), native to Central Asia, has excellent prospects in the development of new cultivars with high anthocyanin content and hybrids that could be widely used in ornamental horticulture.Materials and methods. The collection maintained at Maikop Experiment Station of VIR currently contains 17 different forms of Niedzwetzky’s apple. Most of them were introduced in 1968 from the pomological garden in Talgar, Kazakhstan. Evaluation of their phenological patterns, yield, precocity of bearing, disease resistance, fruit quality, ornamentality, etc. was based on the guidelines developed at VIR.Results and conclusion. Characteristics and specific features for all accessions of Niedzwetzky’s apple are formatted into a table. As a result of testing, the following accessions were identified: k-2389, k-29429, k-29428, k-29430 and k-29422 for their high yield; k-29429 and k-29426 for a large fruit size; k-29429, k-29430 and k-29422 for fruiting precocity; k-29431, k-29423, k-29427 and k-2389 for a pleasant sour-sweet fruit flavor, and a number of forms with medium resistance to apple leaf and fruit scab. Of special interest are the accessions with red and dark red fruit flesh color (k-14948, k-2389 and k-13279): they are most impressive in their flowering and fruiting phases. Niedzwetzky’s apple accessions with red pigmentation are promising for the development of cultivars with higher anthocyanin content in fruit. Besides, M. niedzwetzkyana and its hybrids have good prospects as ornamental plants.